Judge Blaine Pettitt Retirement Luncheon at Fresno Hilton Hotel Ballroom - Watkins, Howard::::::::: (1985)
Stephen Blumberg speaking at lectern; Judge Blaine Pettitt and Alice Pettitt seated at head table